MODEL COOPERATIVE LEARNING TYPE COMPLEX INSTRUCTION (CI) UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN AGRIBISNIS TANAMAN SAYURAN KELAS XI ATPH SMK NEGERI 4 LUWU - Agusprianti, Agusprianti; Rais, Muhammad; Mustarin, Amirah (Jurnal Pendidikan Teknologi Pertanian, 2018)
This study is a classroom action research (Classroom Action Research) aims to determine the learning outcomes of students in the vegetable crop agribusiness subjects by using a complex instruction type cooperative instruction (CI) model. The subjects of this study were the 11th grade students of ATPH SMK Negeri 4 Luwu in the odd semester of 2017/2018 school year consisting of 23 students. This research was carried out for two cycles consisting of activities, namely: planning, implementation, observation, and reflection. Collecting student learning outcomes data is done by using observation sheets and student learning outcomes test sheets. The results of the study show that the initial test of students with an average value obtained is 35.7% and the test in the first cycle (I) the average score is 76.1% while in the second cycle (II) the average score is that is 85.91%.